VIII Festival Iberoamericano de Teatro de Bogotá, marzo 15 al 31 de 2002 - Garavito, Lucía (Latin American Theatre Review, 2002)
VIII Festival Iberoamericano de Teatro de Bogotá, marzo 15 al 31 de 2002